DEVELOPMENT OF INTELLIGENT SYSTEM FOR SOLVING OF IN INDUSTRIAL POLICY BY MONTE CARLO METHOD - Taisiya N. Mironenko; Ekaterina I. Bragina (Статистика и экономика)
The article considers one of the prioritiesin the ﬁeld of artiﬁcial intelligence - Markovchains. The problem of forecasting the strategic investment directions in industrial policy by using a Monte Carlo method issolved.